2008
DOI: 10.1111/j.1600-051x.2008.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the success of sinus floor elevation and survival of implants inserted in combination with sinus floor elevation

Abstract: The insertion of dental implants in combination with maxillary sinus floor elevation is a predictable treatment method showing high implant survival rates and low incidences of surgical complications. The best results (98.3% implant survival after 3 years) were obtained using rough surface implants with membrane coverage of the lateral window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
628
7
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(706 citation statements)
references
References 102 publications
45
628
7
26
Order By: Relevance
“…This study is restricted because of the limited data from controlled trails comparing implant survival in the augmented maxillary sinus and the posterior maxilla. PJE-TURSSON et al 20 studied the surfaces of implants and their failure rate. The best results were obtained using rough surface implants (98% implant survival after 3 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is restricted because of the limited data from controlled trails comparing implant survival in the augmented maxillary sinus and the posterior maxilla. PJE-TURSSON et al 20 studied the surfaces of implants and their failure rate. The best results were obtained using rough surface implants (98% implant survival after 3 years).…”
Section: Discussionmentioning
confidence: 99%
“…The reviews published in the international literature did not have such strict inclusion criteria as the current review 7,10,19,20 . In the current systematic review methodological quality was assessed using specific study-design related forms designed by the Dutch Cochrane Collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been reported that Schneiderian membrane perforation remains the most common complication of sinus augmentation 21 and that one of the factors contributing to this is the thickness of the lateral sinus wall. 12 Perforations may also occur due to irregularities in the sinus wall that range from shallow ridges to crescent-shaped projections and septa of considerable size.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Knowledge of the anatomic structure of the area is important for this procedure. In the present study, we were able to observe the presence and location of the PSAA with CBCT scans.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Sinus augmentation is a safe procedure with high predictability for rehabilitation of severely atrophic posterior maxillae. [3][4][5][6] The branches of the maxillary artery should be taken into consideration during sinus augmentation because of the potential risk of bleeding during the procedure owing to damage to the vascular supply in the lateral wall. 7 Assessment of the maxillary sinus anatomy is important to avoid unnecessary complications due to the close anatomical relationship of the PSAA with the Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%